1978
DOI: 10.1213/00000539-197801000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Central Vagal Control of Fentanyl-Induced Bradycardia During Halothane Anesthesia

Abstract: Six mongrel dogs were used to investigate the mechanism of action of fentanyl-induced bradycardia. With controlled acid-base balance and temperature, and under 1.0 to 1.2 percent endtidal halothane anesthesia, 5 and microgram/kg of IV fentanyl citrate were given sequentially 1 hour apart and heart rate (HR) followed for 60 minutes. A dose-related depression of HR followed both injections. One week later the same dogs were studied similarly, except that bilateral cervical vagotomies were performed before fentan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
54
2
3

Year Published

1984
1984
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(60 citation statements)
references
References 0 publications
1
54
2
3
Order By: Relevance
“…This means that remifentanil exerts central vagotonic action, leading to bradycardia and hypotension. The central vagotonic effect of fentanyl, another µ-opioid receptor agonist, is well documented 8 and, clinically, patients' heart rates slow down after a bolus injection of fentanyl during anesthesia. The central vagotonic effect of remifentanil is short-lived or soon after its onset, it is opposed by increased sympatehtic activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This means that remifentanil exerts central vagotonic action, leading to bradycardia and hypotension. The central vagotonic effect of fentanyl, another µ-opioid receptor agonist, is well documented 8 and, clinically, patients' heart rates slow down after a bolus injection of fentanyl during anesthesia. The central vagotonic effect of remifentanil is short-lived or soon after its onset, it is opposed by increased sympatehtic activity.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that approximately 10% of the bradycardic effect of fentanyl in dogs is attributable to its peripheral action rather than to its central vagotonic action. 8 Electrophysiological study demonstrated that fentanyl exerts a direct negative chronotropic action by stimulating µ-receptors in the rabbit sino-atrial node. 1 3 Thus, remifentanil might have exerted a negative chronotropic action similar to that of fentanyl.…”
Section: Discussionmentioning
confidence: 99%
“…Fentanyl is known to enhance vagal activity, 8,9 which could trigger cough and reflex bronchoconstriction. However, the involvement of a vagal-dependent pathway was not favoured in the previous studies because atropine, an antimuscarinic agent, failed to suppress cough.…”
Section: Méthode : Cent Dix-huit Patients Ont éTé Répartis Au Hasard mentioning
confidence: 99%
“…However, the involvement of a vagal-dependent pathway was not favoured in the previous studies because atropine, an antimuscarinic agent, failed to suppress cough. 2,3 Additionally, possible mechanisms of fentanyl-induced cough include a pulmonary chemoreflex mediated by vagal C-fibre receptors (also known as J-receptors) with its nonmyelinated afferent fibres, 1,10 direct stimulation of the vagal nucleus which augments the bronchomotor tone, 8,9 opioid-induced histamine release, 11,12 the release of neuropeptides after activation of prejunctional µ-opioid receptors by fentanyl and subsequent activation of presynaptic sensory C fibres, 13 and stimulation of the irritant receptors in upper pulmonary mucosa secondary to fentanyl-induced tracheal smooth muscle constriction or bronchoconstriction.…”
Section: Méthode : Cent Dix-huit Patients Ont éTé Répartis Au Hasard mentioning
confidence: 99%
“…Já o sufentanil prolonga a duração do potencial de ação em fibras de Purkinje de cães [24][25][26] . Da mesma forma, Reitan e col. atribuíram 10% da bradicardia, causada pelo fentanil em cães, à sua ação periférica e não apenas vagotônica central 27 . Em ratos, Saeki e col. demonstram a ativação dos receptores opióides tipo mu no nódulo sinoatrial, o que comprovou um efeito cronotrópico negativo direto do mesmo 28 .…”
Section: Discussionunclassified